Model of formation of stress resistance of vocalists-performers in the system of additional professional education - N. V. Solovova; N. V. Sukhankina (Вестник Самарского университета: История, педагогика, филология)
The article deals with the issues of theoretical substantiation of the development of the model of formation of stress resistance of vocalists-performers in the system of additional professional education. The relevance of the problem is determined by the necessity of a systematic approach to the formation of stress resistance of vocalists-performers, taking into account their individual physiological, psychological and professional needs. It is shown that special stress factors of vocal-performing activity determine the presence of the most characteristic types of stress of vocalists-performers (psychoemotional, stage, communicative, physiological). Based on these assumptions, the structure of stress resistance of vocalists-performers is formed, consisting of five components: value-motivational, emotional-volitional, cognitive-technological, reflexive, communicative. The developed model as a set of elements (target, content, process, result), identified on the basis of the principles of systemic, personality-oriented, activity, competence approaches, aims to develop indicators in the structure of stress resistance of vocalists-performers on the basis of the selection of pedagogical means in the system of additional professional education